CCAT1 lncRNA Promotes Inflammatory Bowel Disease Malignancy by Destroying Intestinal Barrier via Downregulating miR-185-3p. Issue 5 (4th January 2019) - Ma, Dan; Cao, Yingying; Wang, Zhenhua; He, Jie; Chen, Huimin; Xiong, Hua; Ren, Linlin; Shen, Chaoqin; Zhang, Xinyu; Yan, Yuqing; Yan, Tingting; Guo, Fangfang; et al.
Abstract: Background: The long noncoding RNA (lncRNA) colon cancer–associated transcript–1 (CCAT1) has been reported to play a vital role in the development of cancer. Although the link between inflammation and cancer initiation is well established, whether CCAT1 is involved in inflammation and promotes inflammatory bowel disease (IBD) malignancy remains undetermined. We aimed to investigate the expression of CCAT1 in IBD and the effect of CCAT1 overexpression on intestinal epithelial barrier function. Methods: The relationship between CCAT1 and the inflammation-related pathway was analyzed in both colorectal cancer (CRC) and IBD patients. Gene expression was detected by real-time polymerase chain reaction and Western blot. Transepithelial electrical resistance (TEER) and FD-4 flux measurement were used to test the effect of CCAT1 and miR-185-3p on intestinal epithelial barrier function. Luciferase assay was performed to validate the target site of miR-185-3p on 3'-UTR of MLCK mRNA. Results: Gene set enrichment analysis revealed that several inflammation-related genes were enriched in the CCAT1 high-expressed group of CRC patients. The relationship between CCAT1 and inflammation activation in IBD patients was further confirmed. CCAT1 expression positively correlated with MLCK, which acts as a protein kinase to phosphorylate myosin light chain and induces tight junction protein distribution, whereas it was negatively correlated with miR-185-3p in IBD tissues. We also determined that CCAT1 overexpression increased Caco-2 monolayer permeability and upregulated MLCK. Furthermore, CCAT1-induced MLCK overexpression and IBD disease progression were significantly attenuated by miR-185-3p. Conclusions: The CCAT1/miR-185-3p/MLCK signaling pathway is strongly activated to destroy barrier function and promotes the pathogenesis of IBD.